2005
DOI: 10.1590/s1413-70542005000100010
|View full text |Cite
|
Sign up to set email alerts
|

Peliculização: desempenho de sementes de soja no estabelecimento da cultura em campo na região de alto garças, MT

Abstract: RESUMOA utilização de tecnologias que possam aderir os produtos fitossanitários com eficiência e ainda melhorar o comportamento fisiológico das sementes em relação ao seu desempenho em campo, pode trazer significativas contribuições para o agricultor. Com o objetivo de avaliar o uso da película de recobrimento, juntamente com dosagens de fungicida, no desempenho de sementes de soja [Glycine Max (L.) Merril] em campo e na qualidade fisiológica e sanitária das sementes produzidas, conduziu-se este ensaio em camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
2
2
0
5
Order By: Relevance
“…Seeds with high initial vigor at sowing were used and it was carried out under controlled conditions of temperature, humidity and substrate free from phytopathogenic organisms. These data corroborate the study of Trentini et al (2005) in which they used good-quality soybean seeds treated with the Tegram® fungicide and coated with the AGL 205 ® polymer when exposed to a favorable environment for rapid and uniform emergence, no significant differences were found for the variables studied between the Control treatment and the fungicide and polymers combination. Thus, it is possible that the benefits of using polymers may be better expressed under uncontrolled conditions.…”
Section: Resultssupporting
confidence: 87%
“…Seeds with high initial vigor at sowing were used and it was carried out under controlled conditions of temperature, humidity and substrate free from phytopathogenic organisms. These data corroborate the study of Trentini et al (2005) in which they used good-quality soybean seeds treated with the Tegram® fungicide and coated with the AGL 205 ® polymer when exposed to a favorable environment for rapid and uniform emergence, no significant differences were found for the variables studied between the Control treatment and the fungicide and polymers combination. Thus, it is possible that the benefits of using polymers may be better expressed under uncontrolled conditions.…”
Section: Resultssupporting
confidence: 87%
“…A resposta a esses materiais de recobrimento depende muito das características de cada espécie, como também dos materiais utilizados para a peliculização (Trentini, 2004).…”
Section: Introductionunclassified
“…The same was observed by Pereira et al, (2005) in film coating on corn seeds, registering a reduction of 2 percentage points in germination potential. In soybean, Trentini et al, (2005), found no significant differences on seeds germination coated with AGL 205 film and fungicide.…”
Section: Resultsmentioning
confidence: 86%